INCONGRUENCIA EN LA REDACCIÓN DEL DELITO DE BANDA CRIMINAL PARA DIFERENCIARLO DEL DELITO DE ORGANIZACIÓN CRIMINAL - CUBA NINAMANGO, NEMESIO ABEL (2020)
Since the terrorist attack on the twin towers, in 2001 in New York, the idea of "Crime Control" has been introduced into the legal-technocratic language (criminal policy), that is, what matters most now is order, therefore, before the manifestations of traditional and conventional crime, the "zero tolerance" rule is applied, which means a maximum of intervention in the sphere of citizen freedom and a gradual and intense relativity of the fundamental guarantees. According to the line noted, the blind flight to criminal law, in turn, affects the staging of the so-called «criminal populism», that is, the political use of criminal law, in terms of obtaining political-sectoral objectives, which they are over exalted in situations of particular public commotion. Peruvian sociologist Lucia Dammert, in an interview in the newspaper La República, before the question What are the simple solutions that do not work (in the problem of Citizen Security? The interviewee said: “Those that do not work are all those that have to do with “criminal populism.” It does not work to increase punishment, it does not work to put the innocent while they wait for punishment, it does not work to treat those who are drug users to jail. to prevent crime. There are thousands of things that do not work. It is not working to tell the police to go for a walk on the street if they do not have a medium of where to go, what to do. In that sense many of the things that are heard and collects, especially in the electoral discussions during the electoral processes, are things that have already been proven wrong, ineffective, even inefficient ” In the words of Miranda Estrampes, to eradicate this populist use, any new criminalization proposal should undergo an effectiveness test; that is, it should be accredited, as a decisive criterion, the plus of utility that in each case will report this call to Criminal Law against all kinds of interventions. To our knowledge, the matter involves submitting the draft Law -in criminal matters- to programmatic and rationality filters, taking into account the legitimate criteria of a democratic criminal law, which require a whole dogmatic and criminological discussion. It must be stated, therefore, that strictly punitive measures will not have any performance in practice, since at all it is extremely draconian criminal legislation, if those who have to prosecute and prevent crime do not have the minimum elements and instruments to effectively contain The unstoppable criminality of today, without a true intelligence strategy, without the provision of modern equipment based on new technology and without well-paid police officers, what is produced in the end is a "Symbolic Criminal Law", without counter-verification. Factual Keywords: Criminal gang, criminal organization